Potencial alelopático de extratos foliares de espécies do cerrado - Gonçalves, Vanessa Damasceno (2016)
Allelopathy is the science that studies the biochemical interactions between any body type. In the literature it is possible to find several studies using native species of the Cerrado, which demonstrated that many have allelopathic potential still unexplored. The objective of this study was to evaluate the allelopathic potential of the leaf extract of K.coriacea, A.edulis, I. laurin, H. obovatus, D.elliptica eS.guianensissobre germination and development of lettuce seeds (Lactuca sativa L.). Extracts were obtained by grinding in a blender 50g of leaves of different species in 500ml of distilled water. From these extracts was obtained by diluting in distilled water to concentrations of 0, 25, 50, 75 and 100% of each species. Bioassays were conducted in a completely randomized design with five levels and four sub-samples of 50 lettuce seeds. The seeds were placed in transparent plastic boxes type "gerbox" on two sheets of blotting paper moistened with the extracts at different concentrations and the amount of twice and half the dry weight of the paper. The boxes were covered and sealed with plastic wrap and kept in BOD incubator at 20 ° C and a photoperiod of 12 hours for seven days. The characteristics evaluated were percentage of germination and abnormal seedlings, germination speed index, shoot length and primary root and fresh and dry weight of seedlings. The extracts did not affect the germination of lettuce seeds and the allelopathic potential was observed in seedling growth characteristics.